Sustainability and Fashion: challenges and results (ModaPalavra e-periódico, 2018)
This is an interview with Rozalia Del Gaudio, Senior Manager of Communication and Sustainability at C&A Brazil. She has an experience of 24 years in the bussiness communication area, working in companies as Vale and Votorantim Group. The following interview was based in her talk during ONDM event – The Fashion Bussiness – which occured on September 19th, 2017, in Camboriú City, Santa Catarina State, Brazil. The questions are related to issues as circular economy, sustainability in fashion and about projects C&A has been practicing considering its global sustainability strategy.
Keywords: communication; fashion; sustainability